Revitalisasi Usaha Kue Khas Kampar: Pendekatan Pemberdayaan UMKM - Fendrik, Muhammad; Antosa, Zariul; Alpusari, Mahmud; Mulyani, Eva Astuti; Guslinda, Guslinda; Munjiatun, Munjiatun; Rizka, Mifta; Fauza, Naila (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This community service activity was carried out with the aim of empowering Micro, Small, and Medium Enterprises (MSMEs) producing Kampar specialty cakes through business development based on local wisdom. The main problems faced by MSMEs include a lack of product innovation, limitations in packaging and digital marketing, and poor business management skills. The methods used included training, mentoring, and the diffusion of science and technology, which was held on September 2, 2025, in Sungai Tonang Village, North Kampar District. The results of the activity showed a significant increase in the motivation, knowledge, and skills of the participants. The training participants gained a very good understanding of cultural values and local wisdom, and had a positive perception of the economic potential of Kampar specialty cakes. Although technical skills and technology utilization were still in the good category, this program succeeded in increasing the capacity of MSMEs in production, packaging, and digital marketing. Overall, this empowerment activity had a positive impact on increasing self-confidence, competitive readiness, and the ability of MSMEs to develop Kampar specialty cake businesses sustainably